Determinants influencing adoption of cloud computing by small medium enterprises in South Africa - Matandela, Wanda (My University, 2017)
Small Medium Enterprises (SMEs) are now recognized as the driving force behind most thriving economies. This is mainly attributed to the role they play in most economies in reducing unemployment and their contribution towards Gross Domestic Product. This means that SMEs should have the right resources to enable them to enhance performance. Choosing the right technology to support their businesses is one of the important decisions that SMEs should make. Understanding the benefits and challenges of different technologies is often a problem for most SMEs. One of the new technologies that has gained prominence in recent years is cloud computing. Even though the value associated with this technology has been widely researched especially for large enterprises, the rate at which SMEs adopt cloud computing still remains low. The purpose of this research sought to explore and describe the determinants influencing the adoption of cloud computing by SMEs in South Africa. The study used Technology Organization Environment (TOE) framework as the theoretical lens in understanding the adoption of Could Computing phenomenon. Further, this qualitative exploratory and descriptive study used semi-structured interviews to collect data from five SMEs based in Johannesburg, Gauteng Province, operating in different industries and belonging to the National Small Business Chamber. The main factors that were identified as playing an important role in the adoption of cloud computing by SMEs are, relative advantage, complexity, compatibility, awareness, trialability, culture, top management support, size, regulation and trade partner relationship. It is worth noting that there was not enough evidence that competitive pressure played a significant role in SME cloud adoption.
Submitted in partial fulfillment of the requirements for the degree of Master of Commerce in Information Systems (Coursework) at the School of Economic and Business Sciences, University of the Witwatersrand, June 2017
Keywords: Business enterprises--South Africa; Small business--South Africa; Technological innovations--Management; Cloud computing